Remapping the Marginal in Contemporary American Immigrant Writing - MATEI, Georgeta (2026)
In the context of globalization and intense intercultural exchanges, the migratory phenomenon is gaining more and more importance in our lives and in relation to the other1. In this thesis, we employ the concept of alterity from a transnational perspective. As it produces a shift towards the mainstream, contemporary immigrant writing in the US today goes beyond the politics of polarity and questions the boundaries of American individuality but also those of American national literature. Eight decades ago, Oscar Handlin suggested that American history is a history of immigrants (1951/ 1973: 3). President John F. Kennedy repeatedly quoted Handlin in his 1959 essay, “A Nation of Immigrants” (1959/ 2017). American history and literature, seen only from a pro-immigrant perspective, are, to an extent, incomplete and undoubtedly open to controversy (Gerber, 2013).